P5.067 The Way to Go Forward in Optimization of STI Management in Eastern Europe: Eastern European Network For Sexual and Reproductive Health (EE SRH). (13th July 2013) - Domeika, M; Ballard, R C; Unemo, M
Abstract : Background: The collapse of the Soviet Union resulted in large changes in the organisation of the health care in many newly independent countries belonging to the WHO European region. Unfortunately, STI management received a highly suboptimal attention. Accordingly, existing professional STI networks were disaggregated by country borders as well as differences in economic and political situations. Many became isolated by their own country and language barriers and financial limitations, and the evidence-based standards elaborated by "Western professional societies" were difficult to access, adhere to and, in general, discuss regarding their appropriateness for the EE countries. Methods: Establishment of the EE SRH; a professional network and bridge between the EE countries and Western European countries and expertise. Numerous of meetings, workshops and trainings to, using international evidence-based approaches, optimise and quality assure diagnosis, treatment and epidemiological surveillance of sexually transmitted and other genital tract infections, as part of the reproductive health disorders. Results: An international network of professionals in STI management was established in 2006 with participation of 15 EE countries. Using evidence-based international approaches, including those elaborated by the CDC, WHO, IUSTI and with the help of internationally acknowledged experts, consensus guidelines for the diagnosis of STIs have been elaborated and internationally published. Those guidelines have also been translated into the national languages and after adaptation published in the national languages and legalised as national STI diagnostic standards in many countries. Strict validation of locally-manufactured cost-effective diagnostic test systems has also been performed. Attempts to establish sustainable surveillance of antimicrobial resistance in gonococci in many of the EE countries is also ongoing. Conclusion: As the next steps, increased implementation of the EE SRH guidelines, establishment of laboratory networks (including STI reference laboratories), and strict monitoring of the achievements are imperative.